State Machine Replication for the Masses with BFT-SMART - Bessani, Alysson; Sousa, Joao; Alchieri, Eduardo E.P. (Proceedings - International Conference on Dependable Systems and Networks, 2014)
The last fifteen years have seen an impressive amount of work on protocols for Byzantine fault-tolerant (BFT) state machine replication (SMR). However, there is still a need for practical and reliable software libraries implementing this technique. BFT-SMART is an open-source Java-based library implementing robust BFT state machine replication. Some of the key features of this library that distinguishes it from similar works (e.g., PBFT and UpRight) are improved reliability, modularity as a first-class property, multicore-awareness, reconfiguration support and a flexible programming interface. When compared to other SMR libraries, BFT-SMART achieves better performance and is able to withstand a number of real-world faults that previous implementations cannot.